Falola 2024. Writing the History of the African Diaspora: Rezension - Monz, Katharina (AAeO - Afrikanistik-Aegyptologie-Online, 2025)
Toyin Falola (2024). Writing the History of the African Diaspora. Elements in Historical Theory and Practice. Cambridge University Press. ISBN 978-1-009-47568-6, € 58,34Online-Veröffentlichung am 14.05.2024, online ISBN 978-1-009-44208-4, DOI: 10.1017/9781009442084, Digitaler Zugang für Einzelpersonen € 19,84